2010
DOI: 10.1073/pnas.1005165107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Ser312 contributes to tumor suppression by p53 in vivo

Abstract: The tumor suppressor p53 is a master sensor of stress, and posttranslational modifications are key in controlling its stability and transcriptional activities. p53 can be phosphorylated on at least 23 Ser/Thr residues, the majority of which are phosphorylated by stress-related kinases. An exception is Ser315 in human p53 (Ser312 in mouse), which is predominantly phosphorylated by cell cyclerelated kinases. To understand the biological importance of Ser312 phosphorylation in vivo, we generated p53Ser312Ala knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…We focused our studies on three main targets of the C/EBP␤-HDAC1 complexes: p53, SIRT1, and PGC1␣, and on consequences of the down-regulation of p53 at late stages of liver cancer. It has been shown that the p53-p21 pathway inhibits liver proliferation and that it is eliminated during development of liver cancer (23,24). However, the mechanism of this elimination has not been shown.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our studies on three main targets of the C/EBP␤-HDAC1 complexes: p53, SIRT1, and PGC1␣, and on consequences of the down-regulation of p53 at late stages of liver cancer. It has been shown that the p53-p21 pathway inhibits liver proliferation and that it is eliminated during development of liver cancer (23,24). However, the mechanism of this elimination has not been shown.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 This residue is phosphorylated by kinases such as cdk2, However when p53 Ser312Ala mice were exposed to a DNA damaging stimulus, opposing results were obtained. Both studies exposed the mice to a single 4 Gy dose of radiation and monitored the mice for tumor development.…”
mentioning
confidence: 83%
“…This mutation did not affect the survival of mice under normal physiological conditions and appeared to have only mild effects on stress-responses in fibroblasts. However, the irradiation of p53 S312A/S312A mice revealed their predisposition to develop thymic lymphomas and liver tumors, and a decreased p53 response was demonstrated in liver tumors (Slee et al, 2010). As for serine 392, in vitro studies revealed its phosphorylation in response to UV irradiation, correlated with p53 activation (Kapoor and Lozano, 1998;Lu et al, 1998).…”
Section: Mutations In the C-terminal Region Of The Proteinmentioning
confidence: 99%
“…Furthermore, whether this phosphorylation regulates p53 functions positively or negatively appeared controversial after in vitro studies (Fogal et al, 2005;Qu et al, 2004;Zacchi et al, 2002;Zheng et al, 2002). Two mouse models expressing p53 S312A (equivalent to a S315A mutation in human p53) were recently reported (Lee et al, 2010;Slee et al, 2010). This mutation did not affect the survival of mice under normal physiological conditions and appeared to have only mild effects on stress-responses in fibroblasts.…”
Section: Mutations In the C-terminal Region Of The Proteinmentioning
confidence: 99%